The Effects of Productivity-Based Learning Activities Toward Ability of Students in Basic Education. - Juithong, Asst.Prof.Dr.Suwana (Saengtham College Journal, 2020)
The objectives of this research were 1) to compare the ability to produce of the students in basic education with the 80 percent, 2) to study students,satisfaction in basic education towards productivity-based learning activities. The sampling is underthe basic education of PathumThani, Phra Nakhon Si Ayutthaya, Ang Thongand Bangkok Provinces by Multi-stage cluster random sampling. The first semester of academic year 2559 the number of 10 group. The tool used in this study is the production lesson plan the IOC value is between 0.67-1.00.The satisfaction used in this study was a guestionnaire which five-rating scale its coefficieint reliability 0.78.The Average Standard Deviation and t-test one sample. The findings were as follows: The ability to produce of the students in basic education level, they were organized by production activities was significance higher than the 80 percent of the established criteria at the statistical significance at the 0.01 level. The results were satisfaction of the students in basic education every school and every class receive the production learning activities, at the highest satisfaction levels (x̅=4.60,S.D.=0.71)